Hope for the Person with Advanced Cancer in Palliative Care - Ramos, Tangriane Hainiski (2024)
Hope is a multidimensional and multifaceted construct intertwined in the process of caring for people with cancer. It is a dynamic, adaptive emotional state essential for transcendence. This study aims to reflect on the hope of individuals with advanced cancer in palliative care. Hope is determined by various intrinsic, functional, socio-affective, psycho-emotional, and therapeutic factors; among others, it is anchored and enhanced by spirituality, propelling the transcendence of adversity imposed by progressive illness and the search for meaning in life. There is a positive relationship between hope and health-related quality of life, as it is part of a dynamic "mechanism" closely associated with biopsychosocial-spiritual well-being. It is important to reflect on the impact of hope on the care of individuals with advanced cancer for holistic planning grounded in the assessment and promotion of hope to assist in achieving balance.